Faux Semblants: A Critical Outlook on the Commercialization of Digital Art - Dejan Grba (Digital, 2023)
Heralded by promises for the long-awaited economic empowerment of digital art and the paradigmatic shift of creative production, the art market’s fusion with blockchain technologies and the crypto economy has polarized opinions among artists, cultural workers, and economists. Its capricious dynamics and exuberance largely shroud the continuation of the art market’s ideology and the reinforcement of the disturbing political vectors of the crypto/blockchain complex. In this paper, I address several interrelated aspects of art tokenization in a compact and comprehensive critical framework that may be useful for a constructive discourse of contemporary digital art. By focusing on the core poetic principles of artmaking—which concern the historically informed autonomy of expression and socially responsible freedom of creative thinking—I identify some of the prospects for advancing digital art towards an ethically coherent and epistemologically relevant expressive stratum. The opening sections Introduction, Markets, and Contrivances outline the art market, its adoption of crypto technologies, and its influences on the production and expressive modes of digital art. Sections Ideologies and Myths describe the ideological and technical issues of the crypto economy, while Shams and Fallouts delve into the conceptual shortcomings and ethical, political, and creative consequences of the standard art tokenization rhetoric. The closing sections Options and Conclusion present the considerations for a productive assessment of blockchain technologies in digital art and summarize some of the alternative approaches for navigating and interfacing with the crypto art world.